2018
DOI: 10.1002/cpp.2192
|View full text |Cite
|
Sign up to set email alerts
|

Mental health disclosure amongst clinical psychologists in training: Perfectionism and pragmatism

Abstract: Results support an approach to communicating about mental health disclosure that incorporates responsibility, interdependency, and transparency. Suggestions for further research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 35 publications
1
31
0
1
Order By: Relevance
“…Put simply, applied psychologists have no immunity to mental health difficulties. Interestingly, American/Canadian graduate students in this sample reported nominally higher prevalence rates of MHDD (88.5%) compared to U.K. trainees (67%; Grice et al, 2018), and American/Canadian faculty exhibited nominally higher prevalence of MHDD (70.5%) compared to what prior research has found for U.K. registered clinical psychologists (63%; Tay et al, 2018). However, across these samples the overall distribution of diagnoses was similar, with depression and anxiety the most commonly reported, and bipolar and psychotic disorders among the least commonly reported diagnoses (Tay et al, 2018).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Put simply, applied psychologists have no immunity to mental health difficulties. Interestingly, American/Canadian graduate students in this sample reported nominally higher prevalence rates of MHDD (88.5%) compared to U.K. trainees (67%; Grice et al, 2018), and American/Canadian faculty exhibited nominally higher prevalence of MHDD (70.5%) compared to what prior research has found for U.K. registered clinical psychologists (63%; Tay et al, 2018). However, across these samples the overall distribution of diagnoses was similar, with depression and anxiety the most commonly reported, and bipolar and psychotic disorders among the least commonly reported diagnoses (Tay et al, 2018).…”
Section: Discussionmentioning
confidence: 66%
“…In perhaps the largest survey of American psychologists' experiences with psychotherapy, conducted over twenty-five years ago (N = 476; Pope & Tabachnick, 1994), 84% of respondents reported having attended therapy as a client, most commonly for depression. In research from the UK, 63% of registered psychologists and 67% of psychology trainees reported lifetime mental illness (Grice et al, 2018;Tay et al, 2018). These studies provide preliminary evidence that mental health difficulties are prevalent within the profession of psychology, particularly among practitioners.…”
Section: Prior Research In Psychology Student and Faculty Mental Healthmentioning
confidence: 75%
See 1 more Smart Citation
“…However, they can also be agents for change and allies of people with mental illness. That may especially apply to situations in which they disclose their experience of own mental health problems to colleagues, patients or others [12]. There is no evidence that attitudes towards people with mental illness are less negative among German-speaking healthcare professionals compared to other countries [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, they can also be agents for change and allies of people with mental illness. That may especially apply to situations in which they disclose their experience of own mental health problems to colleagues, patients or others [12]. There is no difference that negative attitudes towards people with mental illness are lower among German-speaking healthcare professionals compared to other countries [13].…”
Section: Introductionmentioning
confidence: 99%